Stage at Diagnosis and Surgical Management of Breast Cancer at Dumai Regional Hospital, 2020–2025 - Delidios Arimbi; Ami Amelia (Jurusan Farmasi Universitas Negeri Gorontalo, 2026)
Breast cancer remains the most frequently diagnosed malignancy among women and a major contributor to cancer-related morbidity, while late-stage presentation continues to constrain surgical options in many regional referral settings. This study aimed to describe the stage at diagnosis and patterns of surgical management, and to examine the association between clinical stage and type of surgery among breast cancer patients treated at Dumai Regional Hospital, Riau, Indonesia. A retrospective hospital-based study was conducted using medical records from January 2020 to October 2025, with total sampling of eligible cases (n = 137). Variables included age, clinical stage at diagnosis based on the AJCC 8th edition (grouped as stage I–II and stage III–IV), and surgical procedure (conservative surgery, modified radical mastectomy, or biopsy/non-definitive procedures). Descriptive statistics were used to summarise patient characteristics and management patterns. The association between clinical stage and type of surgery was tested using the chi-square test, and effect size was estimated using Cramer’s V. Most patients were aged 40–59 years (58.4%), with a mean age of 52.5 years (SD 11.5), and the majority presented at advanced stages (stage III–IV: 62.8%). Modified radical mastectomy was the predominant procedure (64.2%), while conservative surgery accounted for a smaller proportion. Clinical stage was significantly associated with the type of surgery performed (chi-square = 12.3; df = 2; p 0.001; Cramer’s V = 0.30). These findings indicate a persistent predominance of late-stage presentation in this regional hospital, underscoring the need to strengthen early detection pathways and timely referral to expand eligibility for breast-conserving management.